Field testing and psychometric properties of Thai version of the Boston carpal tunnel questionnaire - Atthakomol, Pichitchai; Nudchapong, Jirawat; Sangseekaew, Kamonwan; Manosroi, Worapaka; Tongprasert, Siam; Wongpakaran, Tinakon; Wongpakaran, Nahathai (Frontiers in Neurology, 2023)
Introduction The Boston Carpal Tunnel Questionnaire (BCTQ) is a widely recommended patient-reported outcome measure to evaluate symptoms and functions in carpal tunnel syndrome (CTS) patients. We aimed to evaluate the translation and cross-cultural adaptation of the Thai version of the BCTQ (Thai BCTQ) and to investigate the psychometric properties including internal consistency, test-retest reliability, construct validity and responsiveness. Methods The Thai BCTQ was field tested with 15 healthy volunteers and 15 CTS patients to evaluate the item-objective congruence of each item. Following that, one hundred and twenty-four CTS patients were included for psychometric evaluation in this study. Internal consistency was assessed using Cronbach’s alpha. Test-retest reliability was examined using the intraclass correlation coefficient (ICC). To evaluate construct validity, Spearman’s rank correlation of the symptom severity scale (Thai BCTQ -S), the functional status scale (Thai BCTQ -F) and the subscales of the Thai MHQ were analyzed. Responsiveness was determined using the standardized response mean (SRM). Results Minor modification of the Thai version was made to better explain the term “tingling”. The Thai BCTQ-S, Thai BCTQ-F and Thai BCTQ demonstrated adequate Cronbach’s alpha values (0.91-0.94) and good test-retest reliability (ICC=0.89-0.98). Regarding related dimensions, a strong correlation (r=0.67, P<0.008) was found between the Thai BCTQ-F and the Function subscale of Thai MHQ as well as between Thai BCTQ-F and the Activities of Daily Living subscale of the Thai MHQ (r=0.75, P<0.008). In unrelated dimensions, there was a relatively weak correlation between the Thai BCTQ-S and the Aesthetics subscale of the Thai MHQ (r=0.32, P=0.0116). The SRM of the Thai BCTQ was 1.46, indicating large responsiveness. Discussion The Thai BCTQ has adequate internal consistency in both the symptom and function scales as well as good construct validity and test-retest reliability indicating it is suitable for evaluating Thai CTS patients. This tool also has a high ability to detect clinically significant changes in symptoms and function over time after receiving conservative or surgical treatment.